2017
DOI: 10.4081/jphr.2017.967
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults Rate Their Mental Health Better than Their General Health

Abstract: Background.Self-rated health (SRH) shows strong associations with measures of health and well-being. Increasingly, studies have used self-rated mental health (SRMH) as a predictor of various outcomes, independently or together with SRH. Research has not firmly established if and how these two constructs differ. We sought to characterize the relationship between SRH and SRMH, and to determine how this relationship differed across subgroups defined by sociodemographic and health-related characteristics.Design an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Finally, while the survey response rate was low, which could limit generalizability, other research on CAPHS has not found response bias to significantly skew results. [26]…”
Section: Discussionmentioning
confidence: 99%
“…Finally, while the survey response rate was low, which could limit generalizability, other research on CAPHS has not found response bias to significantly skew results. [26]…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of SRMH for anticipating future mental health problems rests on the underlying construct it measures, a topic of ongoing discussion (Hoff et al, 1997 ; Levinson & Kaplan, 2014 ; Magwene et al, 2017 ). Research shows that while poor SRMH is correlated significantly with psychiatric diagnoses, it does not serve as a proxy for specific mental illnesses.…”
Section: Introductionmentioning
confidence: 99%